A New Tribological Approach for Lubricated Sliding Contact of Pitted Metallic Curvature Cup. Issue 5 (2nd September 2016) - Razak, D. M.; Samion, Syahrullail; Noorawzi, Nuraliza; Azli, Y.
ABSTRACT: Interest in the development and application of plant-based lubricants for medical use is increasing. This study investigates palm oil lubricants as environmentally friendly and renewable resources to optimize the motion in an ergonomic simulated metal hip prosthesis with modification to the acetabular cup surface. Although metal hip replacements are extensively used, minimizing metal-on-metal friction and wear using safe lubricants requires further investigation. The main physical properties of palm kernel oil and palm fatty acid distillate are considered. The viscosity, wear scar, and coefficient of friction are compared to hyaluronic acid. A modified pin-on-disc tribometer simulates friction and wear on a 28-mm-diameter acetabular cup and microscopy image analysis is used to examine the wear scar. The physical properties of palm oil derivatives reduce friction and wear. In brief, the most significant results of this study include the effect of lubricant and number of pits on wear and friction coefficient. The contribution of this research work is to maintain stability and increase the lifetime of ergonomic metal hip implants.